2013
DOI: 10.1016/j.aller.2012.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and asthma: An association modified by age

Abstract: Obesity was associated with a higher prevalence of asthma in young children, but not in adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…We found that overweight/obese preschool-age children were more than twice as likely as lean preschool-age children to have multiple ED visits, which is supported by other studies demonstrating an increased influence of obesity on asthma at younger ages. [40][41][42] Asthma and obesity affect many children, especially those in urban environments. 5 Although asthma is a common and costly cause for pediatric hospitalization, additional research to clarify the impact of obesity on asthma admission outcomes may help drive asthma prevention and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…We found that overweight/obese preschool-age children were more than twice as likely as lean preschool-age children to have multiple ED visits, which is supported by other studies demonstrating an increased influence of obesity on asthma at younger ages. [40][41][42] Asthma and obesity affect many children, especially those in urban environments. 5 Although asthma is a common and costly cause for pediatric hospitalization, additional research to clarify the impact of obesity on asthma admission outcomes may help drive asthma prevention and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Also Ostrom et al found that obesity is common in adolescents with poorly controlled asthma [31]. Gonzalez-Barcala FJ [33] et al in their studies, observed a correlation between body weight and symptoms of asthma and exercise-induced bronchoconstriction. In our study, obesity was found to be a marginal problem.…”
Section: Discussionmentioning
confidence: 95%
“…But in the study by Tavasoli S et al 30 and Forte GC et al 32 mean age was higher ie, 46.5 years and 51.1 years respectively. Gonzalez Barcala FJ et al 17 concluded that obesity was associated with a higher prevalence of asthma in young children but not in adolescents. This similar finding is observed in this study, none of the adolescents were obese.…”
Section: Discussionmentioning
confidence: 99%